FABRICATION OF AEROSPACE COMPONENTS AND THEIR CHARACTERIZATION USING NON-DESTRUCTIVE EVALUATION METHODS - L MAHESH; K VENKATESH; K KISHORECHAND (International Journal of Innovations in Engineering Research and Technology, 2021)
Composite materials are one such class of materials which play a significant rolein manufacturing of current and future aerospace components. Composite materials are particularly attractive to aerospace and military applications because of their exceptional strength & stiffness to density ratios, their chemical inertness and superior physical properties. Aerospace vehicles which operate at high temperature and high erosion environments need thermal protection to their internal subsystems and components. High Silica Phenolic ablative material is considered in the present study along with engineered ultra high strength steel material. One such kind is Maraging steel casing that is bonded inside with Ethylene Propylene Diene Monomer (EPDM) rubber liner as an ablative liner for thermal protection.In the present work, two different types of artificial defects are created and studied viz., a) ‘Delamination’ between layers of High Silica Phenolic composite liner during fabrication and b) ‘Debond’ between Maraging steel casing and rubber liner interface. Non-Destructive characterization both the above defects was performed using different NDE methods i.e., Radiography Testing, Infrared Thermography and Ultrasonic Testing. A comparative study is made between the results of different methods and techniques therein and the salient features are highlighted.